Analisis Kekuatan Struktur Bangunan Dermaga Kayu di Babo Teluk Bintuni, Papua Barat: Analysis of the Structural Strength of a Wooden Pier in Babo Teluk Bintuni, West Papua - Kamarudin, Adan; Erizal (Departemen Teknik Sipil dan Lingkungan IPB, 2021)
Analysis of structural strength to the conditions of the jetty Port Babo of Teluk Bintuni, West Papua is important to ensure the stability of the against external loads and forces. The purpose of this research is to analyse and evaluate the strength of structures, as well as assess the durability of jetty structures. Modeling using the SAP2000 program corresponds to as built drawing. The results of the calculation of the working load include dead loads, live loads, ship berth, ship mooring force, current force, wave force, and earthquake force. Energy due to ship collision loads and vessel berthing force can be reduced using a fender designed using rubber fenders seibu V300H. The results of the structural analysis show that the number of combined variants is sufficient up to the shape mode 12. The dynamic earthquake shear forces in the x and y directions are still smaller than the static shear forces, so it needs to be multiplied by a scale factor of 2,9. The deviation that occurs in the structure is still smaller than the allowable deviation of 350 mm. Beams are designed using reinforcement with diameter 22 mm and 25 mm. The stress ratio value at the pile meets the pile capacity. It can be said that overall the Babo Teluk Bintuni wharf is safe from the working load.